Observe and report [videorecording (DVD)] - Stephens, Joseph (Warner Bros. Entertainment, 2009)
Bargain hunters at the Forest Ridge Mall are about to get more than they bargained for when a chubby man in a ratty bathrobe starts flashing customers. Security guard Ronnie Barnhardt feels that this is the best thing to happen to him. Catching the flasher might just be his ticket to a real police job and to romance with a hot cosmetics-counter babe. Only one thing stands between Ronnie and destiny and that is the tall, handsome cop who actually knows what he's doing.